Multiple supercontinuum generation based on a single mode-locked seed fiber laser - Amiri, Iraj Sadegh; Hassan, Nor Ahya; Ahmad, Harith (John Wiley & Sons, 2018)
In this work, multiple supercontinuum spectrum generation using single pulsed seed fiber laser is demonstrated. A mode-locked laser that operates at 17.6 MHz repetition rate is filtered into six different wavelengths with 1 nm full-width-half-maximum over the range from 1560.4 nm to 1565.4 nm using a tunable band-pass filter. Each filtered wavelength is amplified and launched into a highly nonlinear medium to generate supercontinuum. The multiple supercontinuum spectra span a bandwidth of over 1000 nm each—in the wavelength range from 1200 nm to 2200 nm.